Notaries' Dual Status as Public Officials and Business Actors in Government Procurement - Giovani Marco Tarani Soba; Iwan Permadi; Endang Sri Kawuryan (Faculty of Law, Merdeka University Surabaya, Indonesia, 2027)
This study aims to analyze the regulatory disharmony concerning the legal status of notaries as both public officials and business actors within the government procurement system and to examine its legal implications for professional independence, equality of opportunity, and contractual justice. This research employed a normative legal research method using statutory and conceptual approaches, with qualitative analysis conducted through library research. The primary legal materials consisted of Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 on the Office of Notary, Presidential Regulation Number 46 of 2025 concerning Government Procurement of Goods and Services, Regulation of the National Public Procurement Agency (LKPP) Number 5 of 2021, and Regulation of the Central Statistics Agency (BPS) Number 7 of 2025 concerning the Indonesian Standard Industrial Classification (KBLI). These legal materials were analyzed using the theories of legal certainty, authority, and justice. The research gap lies in the absence of a comprehensive study examining the normative conflict between the legal framework governing the notarial office and the regulations on government procurement, along with its implications for professional independence, equality of opportunity, and contractual justice. The findings reveal a regulatory disharmony whereby the notarial legal framework recognizes notaries as independent and impartial public officials, whereas government procurement regulations classify them as business actors subject to contractual relationships and competitive procurement mechanisms. This inconsistency has the potential to shift the public-service character of the notarial office, undermine professional independence, create preferential relationships that restrict equal opportunities among notaries, and fail to ensure contractual justice between the government and notaries. The novelty of this study lies in proposing a harmonized regulatory framework for notarial service procurement that preserves the legal status of notaries as public officials within the government procurement system while maintaining the essential principles of independence, impartiality, and public service inherent in the notarial profession.